Discovery of harmalanium halides as anti‐ovarian cancer agents. (16th February 2022) - Choi, Yunha; Ji, Sang Hee; Patil, Vineet; Kim, Eun Hye; Park, Hoyeong; Kim, Seong Hwan; Kim, Pilho
Abstract: Harmala alkaloid (HA) derivatives having 4, 9‐dihydro‐3 H ‐pyrido[3, 4‐ b ]indolium core structure were prepared and their anti‐ovarian cancer activities were explored. In the first screening of 14 compounds, dibenzylated 4e and 4f were found to be active against A2780 ovarian cancer cell line. Further preparation of active analogs led to discover 4f 1 as active as 4f in three ovarian cancer cell lines including cisplatin‐resistant A2780 and SKOV3. Three compounds in 4f series showed single‐digit micromolar GI50 values against A2780 and cisplatin‐resistant A2780 cells. While the mechanism of action for the active compounds turned out to be involved in caspase‐dependent apoptotic cell death, anti‐ovarian cancer activities could be induced by inhibition of AKT Serine/Threonine Kinase 1 (AKT) signaling. This unprecedented scaffold 4 may be optimized further to find out clinically useful compounds for the treatment of ovarian cancers. Abstract : Synthesis of harmalanium halides (2 –5 ) and anti‐ovarian cancer activities were explored, where dibenzylated harmalanium halides 4 exhibited significant inhibitory activities against A2780 and cisplatin‐resistant A2780 cell lines. Data from the mechanism of action studies suggest that anti‐ovarian cancer activities may be obtained through caspase‐dependent apoptotic cell death and AKT signaling pathway.